Ultrasensitive and Selective Electrochemical Detection of Dopamine Based on CuO/PVA Nanocomposite-Modified GC Electrode - A. Mohamed Azharudeen; Arpita Roy; R. Karthiga; S. Arun Prabhu; M. G. Prakash; A. Mohamed Ismail Badhusha; Huma Ali; Khadijah Mohammedsaleh Katubi; Md. Rabiul Islam (International Journal of Photoenergy)
At present, the determination of dopamine (DA) is enormously necessary for the human body. Since then, it has played a crucial role in the brain that affects mood, sleep, memory, learning, and concentration. Dopamine insufficiency is a threat to human health. Dopamine recognition is important to avoid this problem. Copper oxide (CuO) nanoparticles are one of the potentials which can be used in the detection of dopamine level in the sample. In this work, CuO was synthesized by a simple chemical precipitation technique and modified by polyvinyl alcohol (PVA) as a capping agent. The nanomaterials manufactured are used for the detection of dopamine in 0.1 M PBS medium at room temperature. The CuO/PVA-modified electrode shows better electrocatalytic activity than CuO/GCE (glassy carbon electrode). The constructed dopamine biosensor of copper oxide-PVA nanocomposites also has extraordinary selectivity, stability, sensitivity (183.12 μA mM-1 cm-2), and a minimum level detection limit of 0.017 μM, is inexpensive, and has minimal effort and rapid detection of dopamine.